(untitled) (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2024)
This research was conducted at the Salero Basamo Restaurant, Gunungsitoli City. This research aims to successfully determine the Salero Basamo restaurant business in maintaining its existence amidst competition from similar food stall businesses. This research uses a qualitative descriptive method, using data sources, namely observation, interviews, documentation. In the research, determining informants used purposive sampling and snowball sampling techniques to obtain 3 key informants who could provide information related to problems at the research site. The results of this research show that the success of a business in maintaining its existence can be seen from the level of customer satisfaction and competitive advantage.